Production and organization of neocortical interneurons - Sultan, Khadeejah T.; Brown, Keith N.; Shi, Song-Hai (Frontiers in Cellular Neuroscience, 2013)
Inhibitory GABA (γ-aminobutyric acid)-ergic interneurons are a vital component of the neocortex responsible for shaping its output through a variety of inhibitions. Consisting of many flavors, interneuron subtypes are predominantly defined by their morphological, physiological, and neurochemical properties that help to determine their functional role within the neocortex. During development, these cells are born in the subpallium where they then tangentially migrate over long distances before being radially positioned to their final location in the cortical laminae. As development progresses into adolescence, these cells mature and form chemical and electrical connections with both glutamatergic excitatory neurons and other interneurons ultimately establishing the cortical network. The production, migration, and organization of these cells are determined by vast array of extrinsic and intrinsic factors that work in concert in order to assemble a proper functioning cortical inhibitory network. Failure of these cells to undergo these processes results in abnormal positioning and cortical function. In humans, this can bring about several neurological disorders including schizophrenia, epilepsy and autism spectrum disorders. In this article, we will review previous literature that has revealed the framework for interneuron neurogenesis and migratory behavior as well as discuss recent findings that aim to elucidate the spatial and functional organization of interneurons within the neocortex.